Treatment failure among Sub-Sahara African children living with HIV: a systematic review and meta-analysis - Belete Gelaw Walle; Chalie Marew Tiruneh; Moges Wubneh; Bogale Chekole; Amare Kassaw; Yibeltal Assefa; Kelemu Abebe; Zeamanuel Anteneh Yigzaw (BMC, 2024)
Abstract Background Antiretroviral treatment failure is a global issue, particularly in developing countries such as Sub-Saharan Africa. Prior research findings were highly variable and inconsistent across areas. As a result, the goal of this systematic review and meta-analysis was to determine the pooled prevalence of treatment failure among children receiving antiretroviral medication in Sub-Saharan Africa. Methods To find qualifying papers, we searched databases (such as PubMed, Google Scholar, African Journals Online, Scopus, and the Cochrane Library). The data were retrieved using Microsoft Excel and exported to STATA Version 14 for analysis. To check for publication bias, we employed Egger and Begg's regression tests. A random-effects model was used to assess the pooled prevalence of treatment failure due to high levels of variability. Results Following the removal of duplicated articles and quality screening, a total of 33 primary articles were determined to be appropriate for inclusion in the final analysis for this study. Overall, the pooled prevalence of treatment failure among HIV-infected children was 25.86% (95% CI: 21.46, 30.26). There is great variety across the included studies, with the majority of them being conducted in Ethiopia. Cameroon had the greatest pooled prevalence of treatment failure among HIV-infected children, at 39.41% (95% CI: 21.54, 57.28), while Ethiopia had the lowest, at 13.77% (95% CI: 10.08, 17.47). Conclusions The pooled estimate prevalence of treatment failure among HIV-infected children in Sub-Saharan Africa was high. The implementation of national and international policies and strategies on ART clinic care services should be given special focus in order to reduce treatment failure in children living with HIV/AIDS. Trial registration The protocol has been registered in the PROSPERO database under the registration number CRD-429011.